2003
DOI: 10.1159/000070180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Two Modes of Antiandrogen Treatment on Insulin Sensitivity and Serum Leptin in Women with PCOS

Abstract: Androgens are suggested to interact with leptin production and with insulin sensitivity in both polycystic ovary syndrome (PCOS) and obesity. The aim of the study was to follow these interactions along with two forms of antiandrogen treatment. Twenty women with PCOS were treated with ethinylestradiol and high dose of cyproteroneacetate (EE-CA) and 8 with the gonadotrophin-releasing hormone (GnRH) analogue goserelin for 6 months. The patients were divided into a low and a high body weight group and compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Our findings of insignificant associations between leptin and androgen levels are in agreement with previous studies (42,(44)(45)(46). Further supporting a minor relation between testosterone and leptin, Krotkiewski et al (48) found no significant changes of leptin levels during anti-androgen treatment in PCOS.…”
Section: Whr Adjustedsupporting
confidence: 93%
“…Our findings of insignificant associations between leptin and androgen levels are in agreement with previous studies (42,(44)(45)(46). Further supporting a minor relation between testosterone and leptin, Krotkiewski et al (48) found no significant changes of leptin levels during anti-androgen treatment in PCOS.…”
Section: Whr Adjustedsupporting
confidence: 93%
“…However, there were a few studies with other antiandrogenic therapies. Krotkiewski et al found no significant changes in leptin levels during antiandrogen treatment (EE and cyproteroneacetate) in PCOS (45). Nevertheless, in the studies with oral contraceptives including desogestrel (a third-generation oral contraceptive), no change of the leptin levels was observed in normal menstruating women at 3 and/or 6 months of treatment (46,47).…”
Section: Figurementioning
confidence: 98%
“…In a study of 43 hyperandrogenic women (hirsutism alone or PCOS), treated with either GnRH analogues or the androgen receptor antagonists spironolactone or flutamide, the impairment in insulin-stimulated glucose uptake at baseline was partially reversed at 3-4 months post-therapy [77]. Similarly, in two studies each of eight women with PCOS, treatment with GnRH analogues for 6 months resulted in improved insulin sensitivity [79,80]. In contrast, in two studies of 18 women and 17 women with PCOS treated with flutamide for 3 months, insulin-stimulated glucose disposal was unchanged [75,78].…”
Section: Intervention Studies In Women With Hyperandrogenismmentioning
confidence: 99%